Toplum Ruh Sağlığı Hemşireliği - Ertem, Melike; Ersoy Özcan, Berna; Kuzu, Ayşe; Özdemir, Nurgül; Aşık, Elif; Onan, Nevin; Dinç, Sevgi; Utaş Akhan, Latife; Çiydem, Emre; Dil, Satı; Yıldırım, Tuğba; Can Öz, Yüksel; et al. (2023)
-